Acoso escolar y sus implicaciones jurídicas en el cantón Santa Rosa año 2014. - Álvarez Bermeo, María de Fátima (2015)
The ecuadorian education system improves every day different intrinsic aspect in it, this tripartite community of teachers, students and parents are affected directly and negatively by the presence of a new socio phenomenon is bullying in the educational center.